Phylogenomics Identifies a New Major Subgroup of Apicomplexans, Marosporida class nov., with Extreme Apicoplast Genome Reduction. (18th November 2020) - Mathur, Varsha; Kwong, Waldan K; Husnik, Filip; Irwin, Nicholas A T; Kristmundsson, Árni; Gestal, Camino; Freeman, Mark; Keeling, Patrick J
Abstract: The phylum Apicomplexa consists largely of obligate animal parasites that include the causative agents of human diseases such as malaria. Apicomplexans have also emerged as models to study the evolution of nonphotosynthetic plastids, as they contain a relict chloroplast known as the apicoplast. The apicoplast offers important clues into how apicomplexan parasites evolved from free-living ancestors and can provide insights into reductive organelle evolution. Here, we sequenced the transcriptomes and apicoplast genomes of three deep-branching apicomplexans, Margolisiella islandica, Aggregata octopiana, and Merocystis kathae. Phylogenomic analyses show that these taxa, together with Rhytidocystis, form a new lineage of apicomplexans that is sister to the Coccidia and Hematozoa (the lineages including most medically significant taxa). Members of this clade retain plastid genomes and the canonical apicomplexan plastid metabolism. However, the apicoplast genomes of Margolisiella and Rhytidocystis are the most reduced of any apicoplast, are extremely GC-poor, and have even lost genes for the canonical plastidial RNA polymerase. This new lineage of apicomplexans, for which we propose the class Marosporida class nov., occupies a key intermediate position in the apicomplexan phylogeny, and adds a new complexity to the models of stepwise reductive evolution of genome structure and organelle function in these parasites.